Invading the Mediterranean Sea: biodiversity patterns shaped by human activities - Katsanevakis, Stelios; Coll, Marta; Piroddi, Chiara; Steenbeek, Jeroen; Ben Rais Lasram, Frida; Zenetos, Argyro; Cardoso, Ana Cristina (Frontiers in Marine Science, 2014)
Human activities, such as shipping, aquaculture, and the opening of the Suez Canal, have led to the introduction of nearly 1,000 alien species into the Mediterranean Sea. We investigated how human activities, by providing pathways for the introduction of alien species, may shape the biodiversity patterns in the Mediterranean Sea. Richness of Red Sea species introduced through the Suez Canal (Lessepsian species) is very high along the eastern Mediterranean coastline, reaching a maximum of 129 species per 100 km2, and declines towards the north and west. The distribution of species introduced by shipping is strikingly different, with several hotspot areas occurring throughout the Mediterranean basin. Two main hotspots for aquaculture-introduced species are observed (the Thau and Venice lagoons). Certain taxonomic groups were mostly introduced through specific pathways – fish through the Suez Canal, macrophytes by aquaculture, and invertebrates through the Suez Canal and by shipping. Hence, the local taxonomic identity of the alien species was greatly dependent on the dominant maritime activities/interventions and the related pathways of introduction. The composition of alien species differs among Mediterranean ecoregions; such differences are greater for Lessepsian and aquaculture-introduced species. The spatial pattern of native species biodiversity differs from that of alien species: the overall richness of native species declines from the north-western to the south-eastern regions, while the opposite trend is observed for alien species. The biodiversity of the Mediterranean Sea is changing, and further research is needed to better understand how the new biodiversity patterns shaped by human activities will affect the Mediterranean food webs, ecosystem functioning, and the provision of ecosystem services.